The effects of women's joining in paid employment on public place usage: Sakarya Geyve case - Cetin, Reycan; Turkun, Asuman (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
This research is about the effects of women's being a part of paid employment on the usage of public places by using women's daily life experiences. Joining paid labour is a crucial strategy for women's empowerment policies. Working outside means leaving home, private space, and being a part of the public places for women. But creating job opportunities for women is not a magical tool that solves all the gender inequalities, on the contrary, Marxist feminists argue that the gendered structure of labour even expands the gap between genders. And feminist geographers underline that women experience public places with a range of barriers created by the patriarchal form of built environments. Even the women have decent works, it is not easy for women to be in public just because the built environment avoids their needs. But despite this hopeless and adverse framework, microanalyses that focus on female workers from developing countries show that women embrace working outside of the home. And when they have proper conditions, they create their empowerment strategies which are slow but deep and strong. This study aims to reveal these empowerments strategies and the needed necessary conditions from the usage of public place perspective. The study case, Geyve in Sakarya, has rural and urban characteristics at the same time. Patriarchal and religious values are deeply embedded in the place. And these values affect the gender roles, labour, and the usage of public places too. Traditionally, women used to work in the agricultural sector as unpaid workers. And their public place usage is limited. But in the 1990s, two food factories opened in Geyve and offered uneducated women a job opportunity aside from the agricultural sector. Women's participation in paid labour in 30 years changed many dynamics, usage of public places too. The study was conducted with the feminist method, focusing on women's standpoint, to understand these changes from the women's perspective. The main data source of this study is the daily life experiences of blue-collar women. These daily life experiences were obtained through in-depth interviews with twenty two female workers. The factory representatives declared that the majority of the female workers are married with children. For this reason, the interviewees were mainly selected from married women with children. The working conditions are critically important in women's changing behaviours, for this reason, the study focused on a work environment where women work in the same environment with men, under the same conditions, and have the same rights. In this context, the study didn't include Geyve's automotive sector. Because this sector is mostly dominated by men. And the textile sector is also out of the scope of the study for a similar reason. Textile sector workers are mostly female and, there is a strong gender hierarchy in this sector. The food factories, which are built in the 1990s and have 1500 workers together, provide the appropriate conditions for the study. In-deep interviews focused on revealing gendered forms of public places, women's questioning interiorised gender roles, and the reflections of these questionings on public place usage. The study showed that women's strategies diversify based on their marital status, owning children, and age. For example, mothers with school-aged children justify their existence in public places with their motherhood identity. And young and single women prefer the same cafes as college students. Older women with adult children do not care to be in public or themselves, but they admire the youngsters and support their younger female members. There are two important common statements from interviews. All interviewees emphasised that they have the same rights to be in public because they work under the same conditions as men, and earn the same money. And they feel safe when they are surrounded by other females when they are in public places. These two statements show that although the women are aware of the unfair patriarchal form of public places, they don't try to demolish it to get their rights. Instead of resisting, they bargain, negotiate, and create small freedom areas for themselves. Joining paid labour and public life are crucial elements of women's empowerment. But women face many barriers in this way because of the patriarchy. Having local information about the women's struggle and survival strategies can be helpful to create ideal working places, empowerment policies, and place-making choices. Hopefully, this study will be useful to understand women's standpoint and include their needs and struggles during the policy-making processes.
Keywords: Join in paid labour; women's empowerment; public place; gender; Architecture